A NEW DIGITAL TRANSFORMATION FRAMEWORK TO ENHANCE ESG PERFORMANCE FOR PUBLIC LISTED COMPANIES IN MALAYSIA - PSNZ (PSNZ, 2025)
This paper aims to explore whether the trend of digital transformation is driving companies to engage in environmental, social, and governance (ESG) practices. The impact of strategic transformation on firms is all-encompassing, making it difficult to capture the mechanisms of impact on corporate ESG practices. To this end, we con- struct a new theoretical framework that combines slack resources and stakeholder theory. This framework attributes the heterogeneity of ESG practices to differences in the ability and willingness of companies. Using data from Chinese listed companies, we find that the digital transformation is improving ESG performance.